Prognostic value of high-risk human papillomavirus DNA and p16INK4a immunohistochemistry in patients with anal cancer: an individual patient data meta-analysis - Obermüller, Theresa; Hautekiet, Joris; Busto, Maria P.; Reynders, Dries; Belgioia, Liliana; Cats, Annemieke; Gilbert, Duncan C.; Körber, Stefan A.; Mai, Sabine; Meulendijks, Didier; Rödel, Franz; Yhim, Ho-Young; et al. (European journal of cancer, 2021)
Background - High-risk human papillomavirus (hrHPV) types represent the aetiological agents in a major proportion of anal squamous cell carcinomas (ASCC). Several studies have suggested a prognostic relevance of HPV-related markers, particularly hrHPV DNA and p16INK4a (p16) protein expression, in patients with ASCC. However, broader evaluation of these prognostic marker candidates has been hampered by small cohort sizes and heterogeneous survival data among the individual studies. We conducted an individual patient data (IPD) meta-analysis to determine the prognostic value of hrHPV DNA and p16 in patients with ASCC while controlling for major clinical and tumour covariates. - Patients and methods - A systematic literature search was conducted to identify all published studies analysing p16 alone or in combination with hrHPV DNA and reporting survival data in patients with ASCC. Clinical and tumour-related IPD were requested from authors of potentially eligible studies. Survival analyses were performed with a proportional hazard Cox model stratified by study and adjusted for relevant covariates. The study-specific hazard ratios (HRs) for the exposures were pooled using a random-effects model. Kaplan-Meier curves from different studies were pooled per exposure group and weighted by the study's total sample size. - Results - Seven studies providing IPD from 693 patients with ASCC could be included in the meta-analysis. Seventy-six percent of patients were p16+/hrHPV DNA+, whereas 11% were negative for both markers. A discordant marker status was observed in 13% of cases. Patients with p16+/hrHPV DNA+ ASCC showed significantly superior overall survival (OS) compared with patients with p16-/hrHPV DNA- tumours (pooled adjusted HR = 0.26 [95% confidence interval CI, 0.14-0.50]) with pooled three-year OS rates of 86% (95% CI, 82-90%) versus 39% (95% CI, 24-54%). Patients with discordant p16 and hrHPV DNA status showed intermediate three-year OS rates (75% [95% CI, 56-86%] for p16+/hrHPV DNA- and 55% [95% CI, 35-71%] for p16-/hrHPV DNA+ ASCC). - Conclusion - This first IPD meta-analysis controlling for confounding variables shows that patients with p16+/hrHPV DNA+ ASCC have a significantly better survival than patients with p16-/hrHPV DNA- tumours.
Gesehen am 08.12.2021
Im Titel ist "INK4a" hochgestellt